Draft genome sequence of probiotic lactobacillus brevis TUCO-5E, isolated from porcine milk - Quilodrán-Vega, Sandra Rayén (2018)
This report describes the draft genome sequence of Lactobacillus brevisTUCO-5E, a probiotic strain isolated from porcine maternal milk. The reads were generated by a whole-genome sequencing (WGS) strategy on an Illumina MiSeq sequencer and were assembled into contigs with a total estimated size of 2,461,089 bp. A total of 2,455 open reading frames (ORFs) were predicted, including 2,301 protein-coding sequences. The draft genome sequence of L. brevis TUCO-5E will be useful for further studies of specific genetic features and for understanding the mechanisms of its probiotic properties in the porcine host.